Charles H. Osgood of Norwich - Durgan, J. O. (Creator) (Ownership Statement: Mystic Seaport, 1887)
Three-quarter length studio portrait of Norwich businessman Charles H. Osgood, standing. Lifestyle Title supplied by cataloger. Osgood was the owner of the steam yacht Narwhal, built by Robert Palmer & Sons, Noank, 1886-87. Brown mount marked "J. O. Durgan, Norwich, Ct." Some spotting on the print.